Accelerated radiation tolerance testing of Ti-based MAX phases. (December 2022) - Tunes, Matheus A.; Drewry, Sean M.; Arregui-Mena, Jose D.; Picak, Sezer; Greaves, Graeme; Cattini, Luigi B.; Pogatscher, Stefan; Valdez, James A.; Fensin, Saryu; El-Atwani, Osman; Donnelly, Stephen E.; Saleh, Tarik A.; et al.
Abstract: MAX phases have recently attracted significant attention for potential nuclear applications due to their novel properties such as unique hexagonal-compact nanolayered crystal structure, high-machinability due to lower hardness levels than conventional ceramics, and high-chemical inertness. In order for MAX phases to be used in nuclear reactors, two aspects deserve detailed investigations: (i) their phase stability at high-temperatures and (ii) microstructural defect formation and recovery induced by energetic particle irradiation. To date, degradation mechanisms of MAX phases at high-temperatures and following irradiation are largely unexplored fields of research. This work focuses on the evaluation of two Ti-based MAX phases—Ti2 AlC and Ti3 SiC2 —within the context of extreme environments. To accomplish this, a one-of-a-kind comparison between neutron irradiations, performed over a decade of research at the high flux isotope reactor, and heavy-ion irradiations, carried out in situ in a transmission electron microscope, has been conducted. The results show Ti-based MAX phases are prone to accelerated decomposition under the conditions investigated. This questions the hypothesis that MAX phases exhibit high phase stability, especially when used in future nuclear energy systems where energetic particle irradiation is a dominating degradation mechanism. Graphical abstract: Image 1 Highlights: A decade of research on Ti-based MAX phase in extreme environments is presented. Neutron irradiations were performed at the high flux isotope reactor. In situ transmission electron microscope heavy ion irradiations were performed at the MIAMI-2 facility. Ti-based MAX phases are prone to accelerated decomposition in extreme environments. The stability of Ti-based MAX phases for nuclear energy applications is evaluated.